2018
DOI: 10.3906/sag-1711-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of percutaneous nephrostomy and double J stent in symptomatic pregnancy hydronephrosis treatment

Abstract: Background/aim: We aimed to compare the success rate of percutaneous nephrostomy (PCN) and double J stenting (DJS) in the treatment of symptomatic pregnancy hydronephrosis.Materials and methods: Diagnosis and grading of hydronephrosis were performed by urinary ultrasound (USG) and Doppler mode was used for evaluation of renal arterial resistivity index (RI). Patients were divided into two groups according to the method used for the treatment of hydronephrosis: group A (PCN, n = 38) and group B (DJS, n = 46). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…PCN placement and ureteral stent placement are the commonly used methods for treating symptomatic hydronephrosis. While both methods have high success rates, the advantage of PCN placement lies in its ability to be performed under local anesthesia, which is important during pregnancy 9 . All PCN placement procedures in the current study were conducted using only local anesthesia, similar to the protocol described by Kavoussi et al and Khoo et al 3,10 .…”
Section: Discussionmentioning
confidence: 99%
“…PCN placement and ureteral stent placement are the commonly used methods for treating symptomatic hydronephrosis. While both methods have high success rates, the advantage of PCN placement lies in its ability to be performed under local anesthesia, which is important during pregnancy 9 . All PCN placement procedures in the current study were conducted using only local anesthesia, similar to the protocol described by Kavoussi et al and Khoo et al 3,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the operation is complicated, and the exposed catheter falls off easily, disturbing the child (13). Furthermore, indwelling JJS is not easy to misdischarge, which is more suitable for pediatric population (14). Currently, the main disadvantage of an indwelling inner JJS is the difficulty of extra hospitalization that is needed for JJS removal under general anesthesia (4).…”
Section: Discussionmentioning
confidence: 99%
“…The study also compared and analysed the time of re-interventions between PCN versus double-J insertion. It concluded that PCN was more effective and feasible than Double-J insertion as a treatment for symptomatic hydronephrosis in pregnancy, especially since PCN needs less reintervention with a longer time between reintervention, compared to double-J stent insertion [36].…”
Section: Percutaneous Nephrostomy (Pcn) Versus Double-j Stent Insertionmentioning
confidence: 99%